Targeted Protein Depletion Using the Auxin‐Inducible Degron 2 (AID2) System. Issue 8 (9th August 2021) - Saito, Yuichiro; Kanemaki, Masato T.
Abstract: Targeted protein depletion using a conditional degron is a powerful method to probe the role of proteins in living cells because of the speed with which depletion can be induced and its reversibility. The auxin‐inducible degron (AID) is one of the most common degron‐based technologies used in cell biology. We recently established an improved system, called AID2, which involves expressing a mutant E3 ligase subunit, OsTIR1(F74G), and fusing a protein of interest to the mini‐AID (mAID) tag, and that employs a new and more potent ligand, 5‐phenyl‐indole‐3‐acetic acid (5‐Ph‐IAA). The AID2 system overcomes some of the drawbacks associated with the original AID system, i.e., leaky degradation without auxin and the requirement of high auxin doses. With AID2 it is, therefore, now possible to control a degron‐fused protein more precisely, enabling target proteins to be degraded with a half‐life of 10 to 45 min via the addition of a low dose of 5‐Ph‐IAA. Importantly, in AID2, it is not necessary to control the expression of OsTIR1(F74G) for suppressing leaky degradation and a parental cell line constitutively expressing OsTIR1(F74G) can be used for the generation of multiple mAID‐tagged proteins. Here, we describe a protocol for the tagging of endogenous proteins with mAID in diploid HCT116 cells. Our protocol can be applied to other mammalian cell lines and will enhance the utility of AID2 for studying protein functions in living cells. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : Generation of a parental HCT116 cell line expressing OsTIR1(F74G) Basic Protocol 2 : Construction of CRISPR and donor plasmids for tagging endogenous genes Basic Protocol 3 : Generation of cell lines expressing a protein of interest fused with mAID